Essential oil composition of Teucrium scordium L. - Morteza-Semnani, Katayoun (Array, 2007)
Composition of the essential oil obtained from dried flowering aerial parts of Teucrium scordium L. (Labiatae) was analyzed by GC and GC/MS. Fifty-six components were identified in the essential oil of T. scordium. The major constituents of the oil were b-caryophyllene (22.8%), (E)-b-farnesene (10.4%), caryophyllene oxide (8.6%), 1,8-cineole (6.1%) and b-eudesmol (5.1%)